Efeitos da ovariectomia e treinamento de força na concentração tecidual de dopamina e serotonina na via nigroestriatal e mesolímbica de ratas - Duarte, Josiane de Oliveira (Universidade Federal de São Carlos, 2011)
Estrogen is a steroid hormone known to play a role in cellular events important for development, maintenance of body physiology and modulatory actions on central nervous system during life. The aim of this study was to investigate the effect of ovariectomy (OVX) and the intervention of strength training on the tissue concentrations of dopamine (DA) and serotonin (5-HT) in the nigrostriatal and mesolimbic pathways in female rats. Also, check behavioral parameters of exploratory activity in novel environment, in testing of the plus maze (EPM) and open field (CA). Female rats were divided into four groups: Sedentary (Sed- Intact), ovariectomized Sedentary (Sed-OVX) Trained intact (Intact-ExCrônico) Trained ovariectomized (OVX-ExCrônico) (n = 10 per group). We conducted a period of 12 weeks of strength training which consisted of increases in a vertical ladder of 1.1 meters, weight tied to its tail. The sessions were held once every three days with 4-9 and 8-12 uphill climb for motion. The OVX caused changes in tissue concentrations of DA and 5-HT in the mesolimbic and nigrostriatal pathways. However strength training has not been able to revet these changes. In behavioral tests of anxiety were observed behavior and decrease the exploratory activity of rats in the independent training (OVX). The results of this study showed that OVX alters the state of the tissue concentrations of DA and 5-HT but these changes seem to depend on the type of receptor and its topographic distribution. Strength training has not been able to reverse these changes.
Keywords: Neurofisiologia; Comportamento; Labirinto em cruz elevado; Neurorreguladores; Ovariectomia; Dopamina; Serotonina; Via Mesolímbica; Via Nigroestriatal; Ovariectomy; Dopamine; Serotonin; The mesolimbic pathway; Nigrostriatal; CIENCIAS BIOLOGICAS